2016
DOI: 10.1103/physrevd.93.084053
|View full text |Cite
|
Sign up to set email alerts
|

Unique Fock quantization of a massive fermion field in a cosmological scenario

Abstract: It is well known that the Fock quantization of field theories in general spacetimes suffers from an infinite ambiguity, owing to the inequivalent possibilities in the selection of a representation of the canonical commutation or anticommutation relations, but also owing to the freedom in the choice of variables to describe the field among all those related by linear time-dependent transformations, including the dependence through functions of the background. In this work we remove this ambiguity (up to unitary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(74 citation statements)
references
References 49 publications
(68 reference statements)
1
73
0
Order By: Relevance
“…Indeed, as discussed in the previous paragraph, the term of order ω −1 n , if present, turns out to be proportional to the mass of the field and cannot be neglected by any means in the ultraviolet regime. In 3 þ 1 dimensions, we obtained the same result [11], but there it is perhaps more clear since the beginning that the mass cannot be discarded in the ultraviolet regime, because it is the responsible of mixing the two chiralities that the Dirac field has in four dimensions. It is worth mentioning that there exist more similarities between the two dimensionally different problems.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Indeed, as discussed in the previous paragraph, the term of order ω −1 n , if present, turns out to be proportional to the mass of the field and cannot be neglected by any means in the ultraviolet regime. In 3 þ 1 dimensions, we obtained the same result [11], but there it is perhaps more clear since the beginning that the mass cannot be discarded in the ultraviolet regime, because it is the responsible of mixing the two chiralities that the Dirac field has in four dimensions. It is worth mentioning that there exist more similarities between the two dimensionally different problems.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
“…In this paper we have extended previous results on the uniqueness of the Fock quantization of free Dirac fields propagating in certain nonstationary Lorentzian geometries in 3 þ 1 dimensions with compact, connected, and orientable spatial sections [11], to the lower dimensional case of 2 þ 1 dimensions. We have shown that the criterion of invariance of the Fock vacuum under the symmetries of the equations of motion, together with the unitary implementability of a nontrivial dynamics, selects a unique class of unitarily equivalent Fock representations, both for the massive and for the massless fields, once the convention of particles and antiparticles is fixed (up to a finite number of modes at most).…”
Section: Conclusion and Discussionmentioning
confidence: 77%
See 3 more Smart Citations